Fungsi dan Peran Badan Perwakilan dalam Sistem Hukum Tata Negara - Leona Citra Maranatha; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
In Indonesia, the state administration system is regulated in the 1945 Constitution, Laws or Government Regulations in Lieu of Laws, Government Regulations, Presidential Regulations, and Regional Regulations. While the power of authority lies at the national level to the lowest citizen group which includes the MPR, DPR, President and Vice President, Minister, MA, MK, BPK, DPA, Governor, Regent/Mayor, to the RT level. These powerful institutions act as representatives of the voices and hands of the people, because Indonesia adheres to a democratic system. The institution is filled by the people of the country who carry out the government of the country. The general understanding of HTN is a set of rules or rules governing state organizations, state equipment, authority of state equipment, relations between state equipment, and the duties and functions of state equipment. The subjects of HTN are State institutions according to the 1945 Constitution (MPR, PRESIDENT, DPR, DPD, Supreme Court, Judicial Commission, Constitutional Court, and Supreme Audit Agency), officials / figures, and citizens. Of the HTN subjects, there are those who act as representative council which have their own roles and functions. The representative bodies in the HTN are the MPR, DPR and DPD. Representative institutions or the so-called parliament generally has 3 functions, the function of legislation, the function of supervision, and the means of political education. As for the function of parliament according to Jimmly Asshidiqie are the legislative function, the supervisory function, and the representative function.